Surgical Resection of Cerebellopontine Epidermoid Cysts: Limitations and Outcome - Farhoud, Ahmed; Khedr, Wael; Aboul-Enein, Hisham (Journal of Neurological Surgery Part B: Skull Base, 2018)
Objective Epidermoid cysts are benign slowly growing tumors commonly involving the cerebellopontine angle (CPA). The aim of this study was to analyze the surgical limitations, surgical strategies, complications, and outcome of resection of these lesions.Material and Methods The clinical data and outcome of 32 cases operated for CPA epidermoid between 2007 and 2015 were retrospectively analyzed. The mean follow-up period was 42.6 months, and all patients were followed up at least for a whole year.Results There were 15 males and 17 females. The median age was 37.6 years. Headache and cranial nerves dysfunction were the most common presenting symptoms. Surgery was performed in all patients using the standard lateral suboccipital retrosigmoid approach. In three cases, microvascular decompression of an arterial loop was performed in addition to tumor excision. Total resection was accomplished in 19 out of 32 cases (59.4%), subtotal resection in 7 cases (21.9%), and only partial excision was achieved in 6 cases (18.7%). There was no recurrence or regrowth of residual tumor during the follow-up period. We had a single postoperative mortality due to postoperative pneumonia and septic shock. New cranial nerves deficits occurred in 15.6% of cases but were transient in most of them.Conclusion The favorable outcome of total resection of CPA epidermoids should always be weighed against the critical risks that accompany it especially in the presence of tight adhesions to vital neurovascular structures. The retrosigmoid approach is suitable for the resection of these tumors even if they were large in size.
Keywords: cerebellopontine; epidermoid cyst; retrosigmoid approach; outcome